2014
DOI: 10.1136/bmj.g6664
|View full text |Cite
|
Sign up to set email alerts
|

Measuring symptomatic relief in men with lower urinary tract symptoms

Abstract: Most currently used drugs have been given too easy a ride

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Cross-sectional studies suggest that older age increases the risk of nocturia [5], and studies have identified additional risk factors, suggesting a multifactorial etiology [6]. Little is known, however, about patterns of progression and remission of nocturia over time, knowledge of which would facilitate shared decision-making about the initiation and continuation of therapeutic options between patients and healthcare providers [7].…”
mentioning
confidence: 99%
“…Cross-sectional studies suggest that older age increases the risk of nocturia [5], and studies have identified additional risk factors, suggesting a multifactorial etiology [6]. Little is known, however, about patterns of progression and remission of nocturia over time, knowledge of which would facilitate shared decision-making about the initiation and continuation of therapeutic options between patients and healthcare providers [7].…”
mentioning
confidence: 99%
“…7,8 The effectiveness of alphablockers as measured by symptom ratings in randomized controlled studies is the basis for current guideline recommendations. 1,8,9 However, in everyday practice, patients and physicians are more concerned with symptom improvements that reflect shifts in the subjective evaluation of symptoms, which may not be reflected in these symptom scores. The randomized controlled studies on which doctors rely for guidance typically report mean changes in symptom ratings rather than the number of patients who experience improvement, making it challenging for clinicians to predict the likelihood of improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when a prescription for therapy is requested, doctors must depend on the general recommendation to begin alpha-blockers. 1,6,9 Clinically useful information would aid physicians in determining which patients are most likely to improve after using an alpha-blocker.…”
Section: Introductionmentioning
confidence: 99%